Implementasi Sel Surya Sebagai Pelacak Surya Satu Sumbu - Hedy Aditya Baskhara; Ojak Abdul Rozak; Elfirza Rosiana (Universitas Pamulang, Prodi teknik Elektro, 2023)
A solar cell is a semiconductor element that can convert solar energy into electrical energy on the basis of the photovoltaic effect. The solar module is a collection of several solar cells. The power generated by solar cells is influenced by the level of solar radiation and ambient air temperature, the lower the solar radiation, the lower the power generated. So that the power generated by solar cells is always optimal, it is necessary to adjust the position of the sun's light to vary the intensity of solar radiation. The system used for such regulation is called a solar tracker system. This research discusses the performance of solar trackers with solar cells as sensors. The solar tracker captures direct light, the voltage is processed by Arduino and the servo motor acts as a drive to adjust the direction of the solar cell to a direction perpendicular to the sun's light. The input of the system is the position of the sunlight and the output is the direction of the solar cell in degrees. This sun tracking system can show a stable response to the movement of solar cells in accordance with the perpendicular position of sunlight so that the power generated by solar cells can be more optimal. This research succeeded in functioning solar cells as solar tracking sensors.